Try before you buy: a small business employer (SME) perspective of international student mobility in England. Issue 7 (3rd July 2021) - Sutherland, Matthew; Thompson, David; Edirisingha, Prabash
ABSTRACT: Attracting international students has become a strategic priority for UK immigration policy as well as for British universities. However, research shows that there are emergent intercultural barriers that challenge international students' carrier aspirations and inhibit their ability to find employment. Also, small business employers (SMEs) are becoming a significant force in the post-Brexit UK economy and integral to creating innovation and employment opportunities. Despite this significance, we do not know what SME owners view the value of international students and how these perceptual discourses shape international student experience and mobility. In response, this research investigates small business employer discourses relating to international student employability. We base our data collection in strategically important North East of England and draw from semi-structured in-depth interviews with small business employers from the region. Our findings discuss their perception of international students as well as universities and discuss how these prevailing discourses influence international students' employability. We specifically show how socio-cultural dispositions of international students, dominant British employer and market discourses, and universities strategic pursuits interplay and contribute to challenges international students confront within the highly competitive and dynamic higher education environment.